READING DIASPORIC MUSLIMS IN AUSTRALIA IN RANDA ABDEL FATTAH’S DOES MY HEAD LOOK BIG IN THIS? - CAMILIA ANJELINA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Literary work has a relation with the reader because of the essence of literary work for readers. Therefore the quality of literary work based on the assessment of readers. Entitled readers to comment, judge, enjoy and appreciate what they read. The readers have a different way to give respond because the perception or respond based on their background includes their experience, their family, their environment. In this case, this thesis uses the novel of Randa Abdel Fattah with the title Does My Head Look Big In this. Which this novel about racism to Muslims in Australia. The reason for the research is the novel has critical of society in Australia with their perspective of Muslims. Besides that Indonesia is one of the largest Muslim populations. So we have to know how the perception or respond of Indonesias young Muslim to this novel. This research aims to describe how the responds or perception of Indonesia young Muslim to the novel of Randa Abdel Fattah Does My Head Look Big In this. This research using interviews and reading the log. This theory of this research is reading the response, diaspora studies, identity, veil and veiling practice, immigrant Muslims in Australia. The result of the research is showing that readers involves emotional and feeling in their response. Some of the readers feel that the veil is important for women especially Muslims, others felt that the veil is a commitment. therefore, the response of readers it depends on each individual. After the reader read the novel, they have some emotional and feeling to the character in the novel. The readers fell what the character feeling although they just read the novel.